The Impact of Pak and China Cultural influences on CPEC Energy Project Moderating effect in South Asia: A Case Study from Pakistan - Siddiqui, Mehtab Begum; Khokhar, Maryam; Makhdoom, Tayyaba Rafique; Hossain, Md Billal; Ejaz, Sarmad; Ejaz, Faisal; Dunay, Anna (International Journal of Energy Economics and Policy, 2023)
Pakistan is a growing nation working to integrate with foreign business for efficient economic activity. The China Pakistan Economic Corridor is pushing Pakistan’s corporate and industrial sectors to accelerate their strategy and developmental implementation processes in order to stay competitive or outperform it. For this reason, China is setting the pace in the business while Pakistan is gradually embracing CSR. This essay aims to investigate the indirect and direct effects of innovation on corporate social responsibility and business performance in Pakistan’s manufacturing sector. Three years’ worth of panel data were gathered for this. The institutional theory and resource-based theory form the foundation of the theoretical framework. Using the multiple regression technique, the direct and moderating effects were examined. CPEC (China Pakistan economic corridor) is a huge bilateral initiative and developmental project that was started by Pakistan and China, in which the major focus is on the enhancement and modernization of the infrastructure of Pakistan in terms of improving trade with China. Because of CPEC uncountable potential and possible benefits to economic growth and economic development of common people’s lives, the China-Pakistan Economic Corridor (CPEC) has become a huge success not just for authorities but also for ordinary Chinese and Pakistani individuals. It is the biggest and major foreign investment in Pakistan ever conducted by a single country. By being such a source of transporting and moving millions of tons of Chinese products to the Middle East, Africa, and Europe through Gwadar port, CPEC has the potential to significantly connect Pakistan and China. Using an event research method and technique, this study adds to the literature by assessing the influence of CPEC on stock returns. We estimate the continuously compounded returns across sectors to see if this impact varies across sectors. Furthermore, this article aims to determine whether or not the effect of CPEC has been penetrated to a fundamental stage. The median equality test is used to analyze the impact of CPEC on non-financial businesses and enterprises listed on the Karachi Stock Exchange’s quality of financial reporting. The impact of CPEC on the stock market is found to be favorable and encouraging but not considerable, indicating that the stock market’s exceptional performance cannot be ascribed to CPEC. At the national and regional level, the significance and impact of CPEC is also mixed.